Visual Acuity Before and After Treatment in Patients with Chemical Injuries at the National Eye Center, Cicendo Eye Hospital, Bandung from 2010 to 2011 - Laksana, Endi Pramudya; Ratnaningsih, Nina; Farenia S, Reni (Althea Medical Journal, 2015)
Background: Chemical trauma is one of the emergency cases in ophthalmology since it can lead to severe, permanent blindness if not immediately treated. This study aimed to reveal pre- and post-therapy visual acuity on patients with chemical trauma at theNational Eye Center, Cicendo Eye Hospital, Bandung.Methods: This study was performed on 40 patientsâ medical records from the National Eye Center, Cicendo Eye Hospital Bandung from January 2010 to January 2011 as secondary data, using the descriptive retrospective method. The data were divided into two groups: acid and alkali trauma. The collected data were analyzed and presented in tables.Results: Chemical trauma cases were mostly caused by caustic soda (17/40) whereas the least were caused by vinegar (3/40) and commonly occurred on adult patients in the right eye on alkali trauma. Patients with chemical trauma generally had normal eyesight before therapy.The number of patients with acid and alkali trauma who experienced improved eyesight after therapy alkali were similar (3 patients) whileÂ  worsening symptoms occurredÂ  in one patient with alkali chemical trauma from mild to mediumÂ  low vision.Conclusions: There are some improvements of visual acuity after treatment in patients with chemical injuries.Â DOI:Â 10.15850/amj.v2n3.482